Will the “Prosperity of the Population and Son” Affect the Hiring of the “Shopkeeper”?—Research on Succession Decisions of Actual Controllers in Chinese Family Firms - Shi, Xiaofei; Tui, Zhangjing; Zhou, Xiaoyu (Frontiers in Psychology, 2022)
As the Chinese saying goes, “The prosperity of the population and son, the prosperity of the country” implies that the more family members and male offspring there are, the more stable and prosperous the future family will be. Whether professional managers will be employed in the process of family firms succession are mostly discussed in the background of the Principal-agent Theory, and there is a lack of investigation on the influence of family factors on actual controllers. Taking publicly traded Chinese family firms from 2009-2019 as samples, we examined the impact of the characteristics of the actual controller’s children on family firms’ professional management. It is found that the number of children, especially the number of sons, will inhibit the professional management of firms, and this conclusion still holds after the robustness test. Further research shows that sons have a more significant impact on professional management than daughters, and the larger the ownership proportion of the actual controller is, the stronger the correlation between sons' characteristics and professional management is. Our study not only expands the research on the influencing factors of firm succession from the perspective of children’s characteristics, but also enriches the organization theory in the context of family firms, which has practical significance for family firms to make succession planning in advance.